Seroprevalence of hepatitis B surface antigen and associated risk factors among pregnant women - Cetin, Sirin; Cetin, Meryem; Turhan, Ebru; Dolapcioglu, Kenan (The Journal of Infection in Developing Countries, 2018)
Introduction: Hepatitis B infection is a serious global public health problem. The aim of the study was to assess the seroprevalance of hepatitis B surface antigen (HBsAg), as well as the risk factors associated with hepatitis B virus (HBV) infection among pregnant women attending antenatal care clinics of the University Hospital in Antioch, Turkey. Methodology: This descriptive cross-sectional study was carried out between May 2016 and December 2016. The Chi-squared was utilized to estimate the statistical significance of the association between socio-demographic variables and HBsAg status. The results were generated as proportions odds ratio (OR) with their 95% confidence intervals (Cl) and calculated by using both univariate and multivariate logistic regression analysis. Results: The seroprevalence of HBsAg was found to be 2.1%. A significant association was observed between age and HBsAg seropositivity (p = 0.027). History of blood transfusion (AOR = 9.51, 95% CI = 1.92-46.80, p = 0.006), history of hepatitis (AOR = 11.13, 95% CI = 2.02-61.28, p = 0.006), tattooing (AOR = 13.64, 95% CI = 2.52-73.76, p = 0.002) and a history of household/close contact (AOR = 11.10, 95% CI = 1.56-78.65, p = 0.016) were significantly associated with the risk of HBV infection. Conclusions: Data regarding the seroprevalence of HBsAg and risk factors associated with HBV infection in pregnant women plays a crucial role in evaluating the effectiveness of the public health protection policies and the strategies to control the disease.